Processos de fusão e aquisição em Portugal: estudo do caso da aquisição da empresa Obelisco S.A. pela holding desafios SGPS, S.A - Gomes, Pedro José Carvalho Martins (2021)
The actual business global scenario is characterized by globalization and the digital era, that make mergers and acquisitions playing an increasingly important role as a strategic measure of expansion, innovation, and portfolio diversification in order to achieve synergies and consequently creating value for shareholders. The current dissertation aims to study the economic and financial impact on the company Obelisco S.A. due to its acquisition by the holding Desafios SGPS, S.A.. In order to conduct this study, projections were prepared based on the reports and accounts of the company Obelisco S.A. and the holding company Desafios SGPS S.A. where Enterprise Value was estimated using the Discounted Cash Flows methodologies, followed by Economic Value Added/ Market Value Added, Cash-Flow Return on Investment and Market Multiples. The results showed, according to the existing literature that the Discounted Cash Flow methodology cannot be applied to all companies, and this is one of those cases, however it is possible to conclude that there was value creation for its shareholders.